DAYA REGENERASI KALUS DAN TUNAS IN VITRO PADI VARIETAS TARABAS PADA BERBAGAI KONSENTRASI 2,4-D - Wahyu Indra Duwi Fanata; Dalliyah Hadrotul Qudsiyah (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
In Vitro Callus and Plant Regeneration Rate of Tarabas Rice on Several Concentrations of 2,4-D The Agricultural Research and Development Agency and the West Java Provincial Government are developing new superior varieties with Japonica rice standards, namely the Tarabas variety. However, the equivalence of somatic embryogenesis ability of Tarabas rice with original Japonica variety has not been reported. In this study, the frequency of callus regeneration of Tarabas vs Hwayoung rice varieties was compared. Induction of callus from mature embryos with several concentrations of 2,4-D showed the same extent of callus formation in both rice varieties. Callus induced by 1 ppm of 2,4-D showed the higher rate of shoot formation. On the other hand, percentage of callus formation of Tarabas rice was not affected by the increase of 2,4-D concentrations and was able to show 100% regeneration rate at the fourth week in the regeneration medium, although the shoot growth was not as fast as those from medium with 1 ppm 2,4-D. Therefore, these results suggest that Tarabas variety has a somatic embryogenesis capacity equivalent to that of japonica rice and has the potential as research objects in the field of biotechnology. Badan Penelitian dan Pengembangan Pertanian serta Pemerintah Provinsi Jawa Barat mengembangkan varietas unggul baru dengan standar padi Japonica yaitu varietas Tarabas. Namun, kesetaraan varietas Tarabas dengan varietas Japonica asli dalam kemampuan embriogenesis somatik belum dilaporkan. Penelitian ini membandingkan respons kultur jaringan antara beras Tarabas dan padi Japonica varietas Hwayoung. Induksi kalus dari embrio matang dengan beberapa konsentrasi 2,4-D menunjukkan respons pembentukan kalus yang sama pada kedua varietas padi. Kalus yang diinduksi 1 ppm 2,4-D menunjukkan laju pembentukan tunas yang lebih tinggi. Di sisi lain, kalus Hwayoung yang diinduksi konsentrasi 2,4-D yang lebih tinggi menunjukkan penghambatan dalam pembentukan tunas. Di lain pihak, pembentukan kalus padi Tarabas tidak terpengaruh oleh peningkatan konsentrasi 2,4-D dan mampu menunjukkan 100% laju regenerasi tanaman pada minggu keempat di media regenerasi walaupun pertumbuhan tunas tidak secepat pada perlakuan 1 ppm 2,4-D. Karena itu, hasil penelitian ini menunjukkan bahwa varietas Tarabas memiliki kapasitas embriogenesis somatik yang setara dengan padi japonica dan padi Tarabas mempunyai potensi sebagai obyek penelitian di bidang bioteknologi.